Measuring beneficiaries in satellite accounts on social protection - Duncan Coughtrie; Andy Fuller; Paolo Passerini; Corrado Peperoni (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2022)
Satellite accounts on social protection combine monetary and non-monetary data on social protection interventions. In the EU, the European system of integrated social protection statistics (ESSPROS) has been developed progressively since the late 1970s. Demand for data on social benefit recipients is longstanding but has intensified with the emergence of efforts to examine the impact of ageing populations and, more recently, the COVID-19 pandemic. The collection of data on social benefit recipients is, however, beset with methodological obstacles. Consideration of possible approaches to the collection of recipient data, and their relevance when applied across benefits with different characteristics (for example, different durations), demonstrates that there is no 'one-size fits all' solution. Consequently, some flexibility is needed to establish an overarching approach to the collection of data on recipients across the full spectrum of social benefits. Accordingly, the most pragmatic option appears to be to pursue a modular approach whereby sub-sets of benefits to which a single approach can be applied are grouped into modules, and a limited variation in approach is permitted between modules.
Keywords: H55; 330; ESSPROS; social protection; satellite accounts; pension beneficiaries; social benefit recipients